Approach to Adapt a Legacy Manufacturing System Into the IoT Paradigm - Rosas, João Almeida das (2018)
This work has been supported by Faculdade de Ciências e Tecnologia da Universidade Nova de Lisboa, by Uninova-CTS research unit and by national funds through FCT -Fundação para a Ciência e a Tecnologia within the research unit CTS - Centro de Tecnologia e Sistemas (project UID/EEA/00066/2013). The authors would like to thank all the institutions.